Exploring the effect of a lifestyle intervention on cancer risk: 43‐year follow‐up of the randomized Oslo diet and antismoking study. (22nd May 2018) - Botteri, E.; de Lange, T.; Tonstad, S.; Berstad, P.
Abstract: Background/objectives: The Oslo diet and antismoking study showed that counselling for a healthy lifestyle reduced lifelong coronary mortality in high‐risk men. We explored whether the same counselling reduced also cancer risk. Methods: The study randomly allocated males at high coronary risk to either a 5‐year intervention for lifestyle changes (cholesterol‐lowering dietary changes, weight loss and stopping smoking) or a control group (1 : 1) in 1972/73. We explored the incidence and mortality of all cancers and cancer forms related to smoking, BMI or diet up to 43 years after randomization. Results: A total of 595 men in the intervention and 621 in the control group were included. At inclusion median age was 45 years, 588 (48.4%) subjects were overweight (BMI > 25 kg m −2 ) and 925 (76.1%) current smokers. The intervention did not reduce the risk of cancer after 43 years (adjusted hazard ratio (HR) 0.96, 95% confidence interval (CI) 0.80–1.15). In the first 25 years of follow‐up, among the 1088 (89.5%) men who were overweight/obese and/or smokers, the intervention reduced the incidence of those cancer forms related to smoking, BMI or diet (including carcinoma of the respiratory, digestive and urinary tracts; adjusted HR 0.69; 95% CI 0.49–0.99). The intervention had no significant effect on incidence beyond 25 years, or on mortality. Conclusions: The 5‐year counselling for a healthy lifestyle did not reduce the overall cancer risk in the very long term. However, in the first 25 years, the counselling reduced the risk of relevant cancer types in overweight/obese subjects and smokers.